Empowering Womens MSMEs for economic independence based on local wisdom - Yastini, Ni Nengah; Karyati, Ni Ketut; Paramarta, Pande Made Ari Ananta (Bioculture Journal, 2024)
Background: The aim of this research is to analyze the empowerment of women in MSMEs for Economic Independence Based on Local Wisdom. Method: The type of research is analytical survey research. This type of data uses qualitative data. Data sources consist of primary data and secondary data. Data collection techniques using interviews, documentation studies, and observations. The data analysis technique uses descriptive methods with a qualitative approach. Findings: Based on the results of the analysis and discussion, empowerment of the existence of female MSME actors, members of the Jempiring Women's Farmers Group (KWT), Badung Regency, uses the local wisdom of Tri Hita Karana. Conclusion: This is considered capable of increasing economic independence to help family finances with education costs, able to help carry out home renovations and repairs, and able to improve the health of all family members because family finances are already good. Novelty/Originality of this article: The novelty of this research lies in the empowerment model of women's MSMEs that integrates the principles of local wisdom Tri Hita Karana with a modern economic approach. This model combines entrepreneurship training, strengthening social networks, and preserving local cultural values to create a sustainable and competitive MSME ecosystem while maintaining cultural identity.